Improving teacher-made tests through item analysis - Nebres, Seneca N. (1974)
This is an illustration of the process of evaluating and improving test quality through item analysis using the UP Science Education Center Achievement Test for High School Physics as a sample. The instrument was evaluated on the bases of content validity, item characteristics, and reliability.
Thesis (M.A.T.Physics)--University of the Philippines.
Keywords: Educational tests and measurements; Examinations